Olericulture in india - M.K. Rana (LUDHIANA KALYANI, 2008)
This book on vegetable crops includes the techniques and methods for raising vegetable crops along with the knowledge of manures,fertilizersand their compositions.
Potato Tomato Brinjal Hot pepper Cauliflower
Keywords: Vegetable crop production